PENGARUH PERTUMBUHAN EKONOMI DAN KETIMPANGAN TERHADAP KESEJAHTERAAN MASYARAKAT DI KABUPATEN PANGKAJENE DAN KEPULAUAN - Sukri, Sukri Sukri (Universitas Teuku Umar, 2025)
Based on the research results, economic growth and income inequality both influence the level of community welfare in Pangkep Regency. Economic growth (<X1>) has a positive and significant influence on community welfare, with a beta coefficient of 0.652 and a significance of 0.001. This means that increasing economic growth tends to increase welfare. Income inequality (<X2>), as measured by the Gini Ratio, also shows a positive and significant influence on community welfare, with a beta coefficient of 0.193 and a significance of 0.044. This